Overview of IKU Strategic Taxpayer Account Representative to Supportoptimal Tax Revenue - Mochamad Saprudin; Achmad Fauzy (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The Minister of Finance through Regulation of the Minister of Finance Number PMK-45/PMK.01/2021 concerning Account Representative (AR) at the Tax Service Office has determined one of the main tasks and functions of an AR to carry out supervision of the fulfillment of Taxpayer tax rights and obligations. The role of AR as an officer overseeing the implementation of the rights and obligations of taxpayers is very instrumental in supporting tax revenues. The scope of supervision carried out by AR covers four matters, namely Supervision of Annual SPT Reporting, Provision of Tax Data (Declaration Tool), Completion of Requests for Explanation of Data and/or Information (P4DK), and Oversight of Periodic Payments (PPM). The performance of this monitoring activity is used as a benchmark for AR performance which is expressed as the Main Performance Index (IKU) of AR. In this article, we will discuss whether the four KPI AR can optimally support tax revenue or not. The results of this literature review will describe how much influence the KPI has on optimal tax revenue.